Toughening composite master batch as well as preparation method and application thereof

By using the synergistic effect of the continuous phase of rubber particles with core-shell structures in PVC materials and chlorinated polyethylene, the problem that CPE masterbatches cannot simultaneously improve the toughness and mechanical strength of PVC materials in the prior art is solved, and higher toughness is achieved and strength, and improve the dispersion and properties of the material.

CN119119645APending Publication Date: 2024-12-13GUANGDONG XIONGSU TECH GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411157693.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing CPE masterbatch modified PVC materials fail to improve the toughness and mechanical strength of PVC materials at the same time, and the uneven dispersion when the CPE is used is small, resulting in limited toughening effect.

Method used

Rubber particles with core-shell structure are adopted, the core layer is nano calcium carbonate, and the shell layer is nitrile rubber, and rubber particles are coated in the continuous phase of chlorinated polyethylene, which is formed by the synergistic effect of chlorinated polyethylene and nitrile rubber. Toughening composite masterbatch improves the toughness and mechanical strength of PVC materials.

Benefits of technology

It significantly improves the toughness and mechanical strength of PVC materials, delays or terminates crack propagation, enhances the energy absorption capacity of the material, prevents brittle fracture, and improves the compatibility and performance uniformity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005005515610000021
    Figure BDA0005005515610000021
  • Figure BDA0005005515610000041
    Figure BDA0005005515610000041
  • Figure BDA0005005515610000061
    Figure BDA0005005515610000061
Patent Text Reader

Abstract

The invention discloses a toughening composite master batch as well as a preparation method and application thereof, and relates to the technical field of high polymer materials. According to the toughening composite master batch, a continuous phase comprises chlorinated polyethylene, a dispersed phase comprises rubber particles with core-shell structures, core layers of the rubber particles comprise nano calcium carbonate, and shell layers of the rubber particles comprise nitrile rubber. The toughening composite master batch can be used for toughening, reinforcing and modifying a PVC (polyvinyl chloride) material, after the toughening composite master batch is added into the PVC material, the chlorinated polyethylene is dispersed in the PVC material in a net-shaped structure and absorbs a large amount of deformation energy to generate crazing, and the energy is transferred to the three-dimensional net-shaped structure of the micro-crosslinked nitrile rubber of the core layer through the crazing and terminates crazing cracking with the nano active calcium carbonate. Meanwhile, a micro-crosslinking three-dimensional network structure of the rubber particles has certain strength, so that great reduction of the strength of the polyvinyl chloride due to addition of heterogeneous materials is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to a toughened composite masterbatch and a preparation method and application thereof. Background Art

[0002] Chlorinated polyethylene (CPE) is the main toughening and modified filler for polyvinyl chloride (PVC); ideally, during the plasticization process of the PVC substrate into which CPE is introduced, CPE forms a network structure and is dispersed in the PVC substrate. Under the action of tension, it can form a shear band to absorb a large amount of deformation energy, thereby greatly improving the toughness of the PVC blending system. In fact, the introduction of CPE can improve the toughness of PVC materials to a certain extent, but it will affect other properties of the PVC blending system. For example, it will significantly reduce the strength of the PVC blending material, resulting in substandard product performance; the amount of CPE in the PVC blending system can only be controlled at a lower level. However, when the amount of CPE in the system is small, due to the high melt strength, poor fluidity, and uneven dispersion of CPE, the toughening effect of the PVC material is extremely limited.

[0003] Patent CN112592545A proposes a reinforced and toughened polyvinyl chloride composite material and its application, which introduces PVC impact modifier and nitrile rubber into polyvinyl chloride resin, and uses chlorinated polyethylene as PVC impact modifier. By optimizing the components and proportions, the stability of the wood-plastic board is ensured, and the impact strength can reach 90KJ / m; however, it fails to take into account the improvement of toughness and mechanical strength. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and shortcomings of the existing CPE masterbatch modified PVC material, which fails to improve the toughness and mechanical strength of the PVC material at the same time, and to provide a toughened composite masterbatch.

[0005] Another object of the present invention is to provide a method for preparing a toughened composite masterbatch.

[0006] Another object of the present invention is to provide an application of the toughened composite masterbatch in the preparation of a reinforced, toughened and modified PVC material.

[0007] Another object of the present invention is to provide a reinforced, toughened and modified PVC material.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The invention protects a toughened composite masterbatch, wherein the continuous phase comprises chlorinated polyethylene, the dispersed phase comprises rubber particles with a core-shell structure, the core layer of the rubber particles comprises nano calcium carbonate, and the shell layer of the rubber particles comprises nitrile rubber.

[0010] The toughened composite masterbatch of the present invention can modify PVC materials and improve the toughness and mechanical strength of PVC materials. The specific principles and effects are as follows:

[0011] 1. The rubber particles are in a core-shell structure, wherein the core layer includes nano-calcium carbonate and the shell layer includes nitrile rubber. The rubber particles in the core-shell structure maintain the toughness of nitrile rubber while enhancing the overall rigidity by using nano-calcium carbonate. The rubber particles can induce local stress concentration in the polyvinyl chloride matrix. When external stress is applied to the polyvinyl chloride material, the stress concentration point of the rubber particles can guide and change the expansion path of the silver streaks, causing the silver streaks to deflect or terminate around the rubber particles. At the same time, the rubber particles have a high modulus and strength, can effectively absorb and dissipate stress, bear part of the load in the stress field, and are conducive to slowing down or terminating the formation and expansion of the silver streaks. In addition, the calcium carbonate itself is an inorganic substance with high rigidity, and its crystal structure gives it a high hardness and elastic modulus. It can serve as an effective stress concentration point in the polymer matrix, slowing down stress concentration and preventing crack expansion. The spherical structure of the calcium carbonate crystal is more conducive to uniform distribution in the polymer matrix compared to other irregularly shaped structures, further promoting the nucleation and crystallization process.

[0012] 2. The toughened composite masterbatch, wherein the continuous phase comprises chlorinated polyethylene, and the dispersed phase comprises rubber particles having a core-shell structure. On the one hand, the use of chlorinated polyethylene as the continuous phase to coat the rubber particles effectively overcomes the problem of poor compatibility between nitrile rubber and PVC materials. On the other hand, polyvinyl chloride has excellent chemical resistance and mechanical properties, while nitrile rubber has excellent oil resistance and elasticity. When the two are mixed, they can complement each other's advantages and disadvantages to form a composite material with better performance. When chlorinated polyethylene and nitrile rubber are added to the polyvinyl chloride formulation system at the same time, the two toughening materials can form a synergistic toughening effect. The chlorinated polyethylene provides a phase interface effect and silver streak passivation effect, and the nitrile rubber provides a combination of flexible bridging and energy absorption mechanisms for polyvinyl chloride. The synergistic effect of the two can significantly improve the toughness of the overall polyvinyl chloride material.

[0013] In addition, the chlorinated polyethylene continuous phase can passivate the microcrack tips in the PVC body, reduce the stress concentration effect, and thus delay crack propagation. At the same time, silver streaks and shear bands are formed in the PVC body. These microscopic deformation mechanisms can effectively absorb and disperse external impact energy, preventing brittle fracture of PVC.

[0014] In some embodiments, the following components are included in parts by weight:

[0015]

[0016] In some embodiments, the rubber particles include the following components in parts by weight:

[0017] 50-70 parts of nano calcium carbonate, 35-45 parts of nitrile rubber, 3-10 parts of polyethylene wax, 5-10 parts of calcium zinc stabilizer, and 0.1-0.5 parts of cross-linking agent.

[0018] In some embodiments, the cross-linking agent is prepared by compounding a thiadiazole compound and a condensate of n-butyraldehyde aniline in a mass ratio of (3-4):(1-2).

[0019] Preferably, the thiadiazole compound is 2,5-dimercapto-1,3,4-thiadiazole.

[0020] The present invention uses a thiadiazole compound and a condensate of n-butyraldehyde aniline (accelerator 808) as a crosslinking agent, which can promote micro-crosslinking of nitrile rubber during the melting process to form a slight three-dimensional network structure. The network structure wraps nano-active calcium carbonate as a reinforcing agent, thereby improving the strength of the core layer structure.

[0021] In some embodiments, the activated nano-calcium carbonate is made from the following raw material components: 100 parts of nano-calcium carbonate, 0.1-3 parts of stearic acid, and 1-5 parts of coupling agent.

[0022] The invention can effectively open the nano calcium carbonate under the action of stearic acid and a coupling agent, reduce the agglomeration degree of the nano calcium carbonate, and after the activation treatment, the nano calcium carbonate has an oleophilic layer, which can be effectively combined with plastic rubber.

[0023] In some embodiments, the coupling agent is at least one of an aluminate coupling agent, a titanate coupling agent and a silane coupling agent.

[0024] Preferably, the coupling agent is an aluminate coupling agent, a titanate coupling agent and a silane coupling agent in a mass ratio of 1:(0.5-2):(0.5-2).

[0025] Preferably, when the coupling agent is any two of an aluminate coupling agent, a titanate coupling agent and a silane coupling agent, the mass ratio thereof is 1:(0.5-2).

[0026] In some embodiments, the particle size of the nano calcium carbonate is 2000-3000 mesh, preferably 2400-2600 mesh.

[0027] In some embodiments, the rubber particles further include 0.1-1 parts of an antioxidant. The antioxidant is not particularly limited and can be an antioxidant commonly used in the field of nitrile rubber, including but not limited to antioxidant B215 and / or antioxidant B225.

[0028] The present invention provides a method for preparing a toughened composite masterbatch, comprising the following steps:

[0029] S1, melt-blending nano calcium carbonate with nitrile rubber, polyethylene wax, calcium zinc stabilizer and cross-linking agent to obtain rubber particles;

[0030] S2, melt-blending the rubber particles, chlorinated polyethylene, calcium zinc stabilizer, polyethylene wax and oxidized polyethylene wax to obtain the toughened composite masterbatch.

[0031] In some embodiments, step S1 further includes an activation treatment of the nano-calcium carbonate, and the activation treatment includes: using stearic acid and a coupling agent to perform surface activation on the nano-calcium carbonate to obtain activated nano-calcium carbonate.

[0032] In some embodiments, step S1 includes: mixing nano-calcium carbonate and stearic acid, heating to 60-70° C. and stirring evenly, adding a coupling agent and heating to 100-110° C. and stirring evenly to obtain activated nano-calcium carbonate.

[0033] In some embodiments, the mass ratio of the nano-calcium carbonate, stearic acid and coupling agent is 100:(0.1-3):(1-5).

[0034] In some embodiments, in step S2 or S3, the melt blending is performed by twin-screw extrusion at a processing temperature of 130-150°C.

[0035] The invention protects the use of a toughening composite masterbatch in the preparation of a reinforced, toughened and modified PVC material.

[0036] The present invention protects a reinforced and toughened modified PVC material, comprising the following components in parts by weight:

[0037]

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention provides a toughening composite masterbatch that can toughen and enhance the PVC material. After the PVC material is added, the chlorinated polyethylene is dispersed in the polyvinyl chloride material in a network structure, and silver streaks are generated after absorbing a large amount of deformation energy. The energy is transferred to the micro-crosslinked nitrile rubber three-dimensional network structure of the core layer through the silver streaks, and the silver streaks are stopped by nano-active calcium carbonate. In this process, a large amount of energy is absorbed and converted, and the toughness of the PVC substrate is improved. At the same time, the micro-crosslinked three-dimensional network structure of the rubber particles has a certain strength, which reduces the significant decrease in the strength of the polyvinyl chloride caused by the addition of heterogeneous materials.

[0040] The reinforced and toughened modified PVC material of the present invention has a tensile strength of more than 32.44 MPa, an elongation of more than 112%, a bending modulus of more than 2083 MPa, and an impact strength of 9.53 KJ / m at 0°C. 2 above. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0042] The raw materials used in the following examples and comparative examples are as follows:

[0043] Chlorinated polyethylene, brand name CPE-135A, manufacturer is Guangxi Tiandong Jinhua Chemical Co., Ltd.

[0044] Nitrile rubber powder, brand name GM-50, manufacturer is Jingjiang Kanggaote New Material Technology Co., Ltd.

[0045] Polyethylene wax, brand name PE-195, manufacturer is Guangzhou Huanqi Chemical Co., Ltd.

[0046] Oxidized polyethylene wax, brand name AC-316A, manufacturer: Honeywell.

[0047] Stearic acid, brand name SA1801, manufactured by Indonesia Green Treasure Company.

[0048] Nano calcium carbonate, brand name H-110, manufacturer is Guangxi Hemei New Material Technology Co., Ltd., particle size is 2000-3000 mesh.

[0049] Calcium zinc stabilizer, brand name QY-200H7 calcium zinc stabilizer, manufacturer is Guangdong Xinda New Material Technology Co., Ltd.

[0050] Thiadiazole compound, brand name ECHO.A (2,5-dimercapto-1,3,4-thiadiazole), manufacturer is Chengdu Chenye Biotechnology Co., Ltd.

[0051] Butyraldehyde aniline condensate, brand name S-1001, manufacturer is Yantai Hengxin Chemical Technology Co., Ltd.

[0052] Antioxidant, brand name B215, manufacturer is BASF.

[0053] The coupling agent includes a silane coupling agent and an aluminate coupling agent, the brand is R8601, and the manufacturer is Zhejiang Boiling Point Chemical Co., Ltd.

[0054] Examples 1-3

[0055] A method for preparing a toughened composite masterbatch in this embodiment, whose raw material components are shown in Table 1, comprises the following steps:

[0056] S1, mixing nano calcium carbonate and stearic acid evenly, heating to 65°C and stirring at high speed, adding a coupling agent, heating to 105°C and stirring at high speed to obtain activated calcium carbonate;

[0057] S2, adding the activated nano-calcium carbonate and nitrile rubber into a twin-screw for extrusion at a processing temperature of 140° C., and adding the remaining raw material components at the same time. During this process, the nitrile rubber undergoes micro-crosslinking to wrap the nano-activated calcium carbonate, forming rubber particles with a core-shell structure.

[0058] S3, adding chlorinated polyethylene, the rubber particles, calcium zinc stabilizer, polyethylene wax and oxidized polyethylene wax into a twin-screw extruder, the processing temperature is 140°C, and extrusion molding is performed to obtain the toughened composite masterbatch; in this process, the chlorinated polyethylene has good compatibility with the shell layer of the rubber particles, and the continuous phase of chlorinated polyethylene can wrap the dispersed phase of rubber particles to form a heterogeneous mixture with a sea-island structure.

[0059] Table 1 Raw material components of Examples 1-3 (parts by mass)

[0060]

[0061] Examples 4-10 and Comparative Examples 1-4

[0062] This embodiment and comparative example provide a reinforced, toughened and modified PVC material, the raw material components of which are shown in Table 2.

[0063] Table 2 Raw material components (by mass)

[0064]

[0065]

[0066] Among them, toughening masterbatch 1 is the toughening composite masterbatch obtained in Example 1;

[0067] Toughening masterbatch 2 is the toughening composite masterbatch obtained in Example 2;

[0068] Toughening masterbatch 3 is the toughening composite masterbatch obtained in Example 3.

[0069] The preparation method of the reinforced and toughened modified PVC material:

[0070] Step 1: Prepare toughening masterbatch according to the above production process and set aside;

[0071] Step 2: Add polyvinyl chloride and toughening masterbatch into a high-speed mixer, heat up and accelerate stirring to 60°C, then add filler into the high-speed mixer, heat up and accelerate stirring to 105°C, discharge the blended material into a cold mixer, stir the blended material at a low speed and cool it down to 90°C, and transport it to a conical twin-screw extruder;

[0072] The third step: extrusion granulation molding to form the PVC blend material having a toughening effect while maintaining rigidity.

[0073] Performance Testing

[0074] The mechanical properties of the reinforced and toughened modified PVC materials of Examples 4-10 and Comparative Examples 1-4 were tested, and the results are shown in Table 3.

[0075] The test standard for tensile strength is: GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".

[0076] The test standard for elongation is: GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics".

[0077] The test standard for flexural modulus is: GB / T 9341-2008 "Determination of flexural properties of plastics".

[0078] Impact strength test standard: GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics".

[0079] Table 3

[0080]

[0081] As can be seen from Table 3, the tensile strength of the reinforced and toughened modified PVC material of the present invention is above 32.44Mpa, the elongation is above 112%, the bending modulus is above 2083MPa, and the impact strength at 0°C is 9.53KJ / m 2 At the same time, with the increase of toughening composite masterbatch content, the tensile strength and flexural modulus decreased, while the elongation and 0℃ impact strength increased significantly.

[0082] Comparing Examples 7, 9-10, it can be seen that when toughening masterbatch 1 is used, its tensile strength, elongation, bending modulus and 0°C impact strength are significantly improved, proving that the nano calcium carbonate used as the core layer of the present invention can effectively reduce its aggregation in the polymer matrix after activation treatment, thereby reducing its adverse effects on material properties. At the same time, the use of thiadiazole compounds and n-butyraldehyde aniline condensate to prepare a crosslinking agent can promote the formation of a micro-crosslinked structure of nitrile rubber during the melting process and improve rigidity.

[0083] Comparing Comparative Example 3 and Example 6, or comparing Comparative Example 4 and Example 8, it can be seen that when the addition amount of the toughening composite masterbatch and CPE is increased and the tensile strength is close, the addition amount of the toughening composite masterbatch is much higher than the addition amount of CPE, so that the elongation and 0°C impact strength are significantly higher. It is proved that the toughening composite masterbatch of the present invention can effectively reduce the decrease in the strength of polyvinyl chloride caused by the addition of heterogeneous materials, and realize that the addition amount of the toughening composite masterbatch can be greatly increased on the basis of meeting the strength requirements of the PVC material, thereby improving the toughness of the PVC material.

[0084] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A toughened composite masterbatch, characterized in that: The continuous phase comprises chlorinated polyethylene, the dispersed phase comprises rubber particles with a core-shell structure, the core layer of the rubber particles comprises nano calcium carbonate, and the shell layer of the rubber particles comprises nitrile rubber.

2. The toughened composite masterbatch according to claim 1, characterized in that: The composition includes the following components in parts by weight:

3. The toughened composite masterbatch according to claim 1 or 2, characterized in that: The rubber particles include the following components in parts by mass: 50-70 parts of nano calcium carbonate, 35-45 parts of nitrile rubber, 3-10 parts of polyethylene wax, 5-10 parts of calcium zinc stabilizer, and 0-0.5 parts of cross-linking agent.

4. The toughened composite masterbatch according to claim 3, characterized in that: The cross-linking agent is prepared by compounding a thiadiazole compound and a condensate of n-butyraldehyde aniline in a mass ratio of (3-4):(1-2).

5. A method for preparing the toughened composite masterbatch according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, melt-blending nano calcium carbonate with nitrile rubber, polyethylene wax, calcium zinc stabilizer and cross-linking agent to obtain rubber particles; S2, melt-blending the rubber particles, chlorinated polyethylene, calcium zinc stabilizer, polyethylene wax and oxidized polyethylene wax to obtain the toughened composite masterbatch.

6. The method for preparing the toughened composite masterbatch according to claim 5, characterized in that: Step S1 also includes an activation treatment of nano-calcium carbonate, and the activation treatment includes: using stearic acid and a coupling agent to perform surface activation on the nano-calcium carbonate to obtain activated nano-calcium carbonate.

7. The method for preparing the toughened composite masterbatch according to claim 6, characterized in that: The mass ratio of the nano calcium carbonate, stearic acid and coupling agent is 100:(0.1-3):(1-5).

8. The method for preparing the toughened composite masterbatch according to claim 5, characterized in that: The temperature of melt blending in step S1 or S2 is 130-150°C.

9. Use of the toughened composite masterbatch according to any one of claims 1 to 4 in the preparation of a reinforced, toughened and modified PVC material.

10. A reinforced and toughened modified PVC material, characterized in that: The composition includes the following components in parts by weight: The toughened composite masterbatch is the toughened composite masterbatch according to any one of claims 1 to 4.

Citation Information

Cited By

  • High-strength toughened modified polyvinyl chloride pipe material and preparation method thereof

    CN122647838A